Uncovering Trends in Psychological Empowerment: Empowering Insights Through Comprehensive Exploration and Advanced Data Analysis - Fika Wulan Meilana Putri; Sri Handari Wahyuningsih (Jurnal Locus Penelitian dan Pengabdian, 2026)
This research aims to analyze trends in psychological empowerment, particularly in companies engaged in the technology industry, innovation, start-ups, creative industries, employee development, and customer service-oriented sectors. Companies such as Google, Apple, Airbnb, Pixar, Deloitte, Zappos, Ritz-Carlton, and Southwest Airlines have demonstrated that psychological empowerment plays an important role in improving service quality, reducing workplace stress, and fostering a positive work culture all of which contribute to the long-term success of an organization. This research employed a qualitative method with a bibliometric analysis approach. Data were sourced from Scopus using the keyword "Psychological Empowerment," yielding 356 documents spanning the period 2014–2023. This study found that psychological empowerment has received increasing attention in the organizational literature, with the number of publications growing steadily each year. Key findings indicate that psychological empowerment plays an important role in improving employee performance and job satisfaction, enhancing loyalty, reducing stress, and encouraging creativity and innovation. Furthermore, empowering leadership and an inclusive organizational culture were shown to have a positive impact on psychological empowerment. This study also highlights the importance of organizational justice, noting that imbalances in perceived fairness from certain sources can be offset by other sources. These findings underscore the value of creating a work environment that supports empowerment as an organizational strategy for improving performance and retaining employees.